Observation of a robust and active catalyst for hydrogen evolution under high current densities - Yudi Zhang; Kathryn E. Arpino; Qun Yang; Naoki Kikugawa; Dmitry A. Sokolov; Clifford W. Hicks; Jian Liu; Claudia Felser; Guowei Li (Nature Communications, 2022)
The development of robust catalysts that could work under industrial-scale current densities is a challenge for hydrogen production. Here, the authors report an in-situ activation method to produce ferromagnetic Ru clusters that can catalyze the hydrogen evolution reaction at high current densities.